Lives and Livelihoods : Post-Crisis Paradigm Shifts in Economic Theory and Practice - Botos, Katalin (Public Finance Quarterly, 2020)
Crisis triggers change in economic theory, this time bringing healthcare to the forefront of attention. We now have our primary focus on finding a cure, and developing treatment as well as preventive capacities. While saving lives is of utmost interest, securing livelihood is also a priority, particularly amid a major economic recession caused by lockdown measures introduced to contain the spread of the virus. The extent of the recession varies in different regions of the world, often because they have very different financial resources to commit to protection. This study focuses on the USA, Europe and the emerging world. It draws the conclusion that taking effective action against the pandemic crisis requires greater international cooperation. It reminds us that the crisis cannot be solved by monetary policy alone. It calls for the use of fiscal policy, as well. All this will most likely have a major impact on and trigger the change of the rules of financial system.